2023
DOI: 10.1186/s13102-023-00624-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between physical activity and quality of life in entrepreneurs from Wrocław, Poland

Abstract: Background Limited physical activity is one of the main reasons for the rapid increase in the prevalence of diseases of affluence, which can lead to premature deaths in adults. Quality of life may be one of potential determinants of physical activity. The aim of this article is to identify the relationships between physical activity and quality of life in entrepreneurs from Wroclaw, Poland. Methods A cross-sectional study was conducted on a group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Students engaged in physical activities had lower smoking addiction scores compared to those who were not engaged in physical activities. This suggests that being physically active may have a positive influence on reducing smoking addiction and improving overall quality of life as previous research showed [66,45,67].…”
Section: Other Social Correlatesmentioning
confidence: 57%
“…Students engaged in physical activities had lower smoking addiction scores compared to those who were not engaged in physical activities. This suggests that being physically active may have a positive influence on reducing smoking addiction and improving overall quality of life as previous research showed [66,45,67].…”
Section: Other Social Correlatesmentioning
confidence: 57%